Cytokine expression in rhinovirus- vs. respiratory syncytial virus-induced first wheezing episode and its relation to clinical course - Hurme, Pekka; Komulainen, Miisa; Tulkki, Marleena; Leino, Annamari; Rückert, Beate; Turunen, Riitta; Vuorinen, Tytti; Akdis, Mübeccel; Akdis, Cezmi A.; Jartti, Tuomas (Frontiers in Immunology, 2022)
Rhinovirus (RV) and respiratory syncytial virus (RSV) are common causes of bronchiolitis. Unlike RSV etiology, RV etiology is associated with a markedly increased risk of asthma. We investigated cytokine profiles of RV- and RSV-induced first wheezing episode, and their correlation with prognosis. We recruited 52 sole RV- and 11 sole RSV-affected children with severe first wheezing episode. Peripheral blood mononuclear cells (PBMCs) were isolated during acute illness and 2 weeks later and stimulated in vitro with anti-CD3/anti-CD28. Culture medium samples were analyzed for 56 different cytokines by multiplex ELISA. Recurrencies were prospectively followed for 4 years. In adjusted analyses, cytokine response from PBMCs in RV group was characterized by decreased expression of IL-1RA, IL-1b, and MCP-1 and increased expression of Eotaxin-2, TARC, and ENA-78 in the acute phase, and increased expression of fractalkine in the convalescent phase compared to the RSV group. An analysis of the change in cytokine expression between study points revealed increased expression of fractalkine and IL-1b and decreased expression of I-309 and TARC in the RV group compared to the RSV group. Considering hospitalization time, a significant non-adjusted group × cytokine interaction was observed in levels of IFN-gamma, MDC, IL-1RA, and VEGF indicating that higher expression of cytokine was associated with shorter hospitalization time in the RSV group, but not in the RV group. A significant interaction was also found in IL-6, but the cytokine response was not associated with hospitalization time in RSV- or RV-groups. In the RV group increased expression of I-309 (CCL1) and TARC were associated with fewer relapses within 2 months, and decreased expression of IL-13 and increased expression I-309 (CCL) were associated with less relapses within 12 months. Differences in cytokine response from PBMCs were observed between RV- and RSV-induced first severe wheezing episode. Our findings also reveal new biomarkers for short- and medium-term prognosis in first-time wheezing children infected with RV or RSV.